Pemodelan Spasial Kesesuaian Lahan pada Blok Agroforestri Kawasan Hutan dengan Tujuan Khusus, Universitas Gadjah Mada - Emma Soraya; Senawi Senawi; Wahyu Wardhana; Bekti Larasati (Faculty of Forestry Universitas Gadjah Mada, 2022)
The species' determination to rehabilitate and enhance the villagers' prosperity needs information on land characteristics, plants' growth requirements, and financial prospects. This study aimed to model the suitability of forest plants, fruit plants, and agriculture crops that are in-situ, desired by the community, and has prospecting financial return based on the biogeophysical characteristics of the Agroforestry Block of the Gadjah Mada University’s Teaching Forest (KHDTK UGM). The land suitability resulted from matching land mapping unit (LMU) characteristics and the plant's growth requirements. The overlay of slope and soil maps generated LMUs. Soil samples were taken and analyzed to identify the characteristics of each LMU. This research suggested that the highest suitability of planting patterns would result in higher land productivity and community prosperity. The Agroforestry Block with the S2 suitability class covered only 26.64% of the area. The land characteristics that inhibit the suitability were solum depth, slope, texture, pH, N, P2O5, and drainage. This research suggested that agroforestry planting patterns in the S2 suitability class should combine timber species (teak and mahogany), Leguminosae (lamtoro and gamal) to improve land quality and as the source of cattle fodder, fruits (jack fruit and mango), and farm crops such as pineapple,..